Optimization of Soxhlet Extraction of Candlenut Oil (Aleurites moluccana (L.) willd) Using Factorial Experimental Design Level 23 - Fachrina, Salsabila; Broto, R. T. D. Wisnu (Vocational College of Universitas Diponegoro, 2023)
Candlenut (Aleurites moluccana (L.) wild) is a plant of the Euphorbiceae family. Candlenut oil is obtained by extracting the oil content in candlenut seeds. Soxhlation is an effective method for solvent extraction, ensuring continuous contact between the solvent and the material to extract the oil efficiently while maintaining the purity of the solvent. In this study, optimization of candlenut oil extraction was carried out using the factorial experimental design level 23. Using this method, it can be determined that the extraction time is the most influential variable in the candlenut oil extraction process. The results showed that the optimum operating conditions were an extraction time of 185 min, a candlenut seed powder size of 20 mesh, and a ratio of material-solvent ratio of 1:6 g/g, resulting in an oil yield of 43.2%. The analysis of candlenut oil conducted at an extraction time of 185 min revealed the following results: a refractive index value of 1.4736, a moisture content of 0.08% bb/b, which complies with the standard SNI 01-4462-1998 for candlenut oil, a viscosity of 15.47 Cp, and a density of 0.869 g/mL. The analysis of the free fatty acid number of 2.4%bb/b and saponification number of 181.55 mg KOH/g is not consistent with SNI 01-4462-1998 candlenut oil.